Casos y cosas: semanario popular (Vol. 1, No. 23) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Los desbordes de la "Troncha", Siquiera el sombrero..., La sesiones borrascosas de la Liga Loretana, Liga Troncha Badani, Ilusiones perdidas, Esos frailes....., Otro frcaso del doctor Badani, Carta a..... Etelvina, Prisiones inmotivadas, Retrazos, nuestro «homenaje», casos y cosas, el milagro del santo, nociones de esgrima, Enamorado?, esta Ud, de novio?, Liga Loretana, aire, mar y tierra.

ENGLISH: The overflows of the "Troncha", Even the hat..., The stormy sessions of the Liga Loretana, Liga Troncha Badani, Lost illusions, Those friars ....., Another case of Dr. Badani, Letter to ..... Etelvina, Unmotivated prisons, Portraits, our "homage", cases and things, the miracle of the saint, fencing notions, In love, are you in love, Loretana League, air, sea and land.
Cases and things: popular weekly (Vol. 1, No. 23)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas